Peritonitis as a Complication of Diverticular Disease of Colon.: Concept, Strategy and Experience - Asiner, Boris; Asiner, Boris; Armand Ugon, César; Rodríguez de Vecchi, Victoriano (Cirugía del Uruguay, 1979)
The paper contains an account of the author's personal experience on peritonitis as a complication of diverticular colopathy.